Karakteristik Kimia Dan Organoleptik Kerupuk Ubi Jalar Ungu (Ipomoea batatas L.) Dengan Penambahan Tepung Ikan Teri (Stolephorus sp.) - Purwokanti, Nining; Augustyn, Gelora H; Ega, La (Tropical Small Island Agriculture Management, 2023)
This study aimed to find the best treatment for purple sweet potato crackers with anchovy (Stolephorus sp) flour. In this study, a single-factor completely randomized experimental design (CRD) was used. The treatment levels were as follows: P0 (control), P1 (5%), P2 (10%), and P3 (15%), which were repeated three times with three replicates of analysis. Moisture content, ash content, fat content, protein content, and carbohydrate content were all measured. The observed sensory parameters, namely taste, color, aroma, and crispness, were descriptively analyzed. The addition of anchovy flour had a very significant effect on the chemical and sensory characteristics, according to the results. P3 treatment (30 percent anchovy addition) provided the best treatment, with a moisture content of 7.91 percent, ash 4.87 percent, fat 14.74 percent, protein 7.64 percent, and carbohydrates 62.40 percent, and a level of preference for taste (3.1), scent (3.1), and crispness (3).